Preparing Student Nurses as Parent‐based Adolescent Sexual Health Educators: Results of a Pilot Study. Issue 2 (31st March 2016) - Santa Maria, Diane; Markham, Christine; Crandall, Stacy; Guilamo‐Ramos, Vincent
Abstract: Objectives: While health promotion and patient education are central to the scope of practice of professional nurses, they often feel ill‐equipped to assume the role of sexual health educator and lack adequate knowledge and skills to effectively engage parents in adolescent sexual and reproductive health efforts. Design and Sample: Employing a mixed‐methods study consisting of both pre‐ and post‐test survey and exit interviews, a pilot study was conducted to assess the impact of implementing a parent‐based adolescent sexual health intervention on baccalaureate nursing student outcomes ( N = 31). Results: We found statistically significant improvements in student outcome expectancies of parenting strategies, barriers to sexual health communication, self‐efficacy, and sexual health counseling experience. Using thematic content analysis of exit interview content, emerging themes were (1) need for increased sexual and reproductive health (SRH) preparation, (2) wanting greater experience and opportunity for involvement in nursing research, and (3) educational gaps in family‐focused community public health. Conclusions: Incorporating adolescent sexual health education into public health nursing clinical training can prepare nurses as parent‐based adolescent sexual health educators, a core competency for nurses working with families in communities and across all health care delivery settings.